17. STUDY ON VAGINAL DRYNESS IN POSTMENOPAUSAL WOMEN AT DA NANG CITY AND SOME RELATED FACTORS IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Surveying vaginal dryness rate and factors associated with vaginal dryness in postmenopausal women at Da Nang City. Subject & method: A cross-sectional study was conducted on 850 postmenopausal women, seen at 17 Health station of 17 wards in Danang City from August to September, 2023. Research was carried out by gynecological examination, test of serum estradiol concentration, collect BMI index and questionnaire for each researching object to investigate vaginal dryness rate and factors associated. Results: Vaginal dryness rate was 49,3%. There was a relationship between serum estradiol concentration with vaginal dryness, menopause time with vaginal dryness, intercourse activity with vaginal dryness, painful in intercourse activity with vaginal dryness, vaginal pH with vaginal dryness. Conclusion: The vaginal dryness rate in postmenopausal women was relatively high. There was an association between serum estradiol concentration, menopause time, intercourse activity, vaginal pH with vaginal dryness.
Keywords: Vaginal dryness, relationship, Danang City.